DEGRADASI SELF-CHARACTER PEMUDA BANJAR: TELAAH SKALA KESOPANAN BERELAAN DALAM MASYARAKAT BANJAR DAN TINJAUAN AL-QUR’AN - Noor Annisa Fajriani; Mushlihati Mushlihati (Sekolah Tinggi Agama Islam (STAI) Al-Wahliyah Barabai, 2023)
Banjar society is very thick with religious values and cultural customs, both in interaction and communication. However, nowadays the value of politeness begins to decline. This study aims to understand the value of the politeness scale of willingness and instilling self-concept of character in Banjar youth and to identify the content of the meaning of will in studying the Qur'an from time to time in Banjar society. This study uses qualitative research with a literature study approach. The results of this study found that the values contained in the meaning of volunteerism are the values of tawadhu, qana'ah, resignation, sincerity, gratitude, and forgiveness. This content can be revived by mengaji beduduk reading as contained with papadah of Banjar scholars such as Prince Antasari, Sheikh Muhammad Arsyad Al-Banjari, and Guru Sekumpul